Frozen landscapes: climate-adaptive design interventions in Ladakh and Zanskar. (16th November 2016) - Clouse, Carey
Abstract: During the course of the past three decades, a number of subsistence agricultural villages in the Himalayan mountain range have witnessed ever-shrinking glaciers and an increasingly erratic supply of glacial meltwater. Having relied on these relatively stable reserves for crop irrigation for centuries, today's high-Himalayan farmers must now contend with irregular weather patterns and events, such as drought, mudslides and cloudbursts. In the face of this shifting landscape, many farming villages have responded by altering long-standing agricultural practices in an effort to adapt to a changing climate. In this context, the incorporation of frozen landscape infrastructures can help to control the flow of surface meltwater, direct valuable water resources and stockpile irrigation reserves in the form of ice and snow. This article describes three types of frozen landscape design interventions currently employed in northern India: artificial glaciers, ice stupas and snow barrier bands. Although these constructs have been designed by engineers rather than landscape architects, they contribute to a larger body of climate-adaptive design solutions that suggest a way forward in the face of the unstable environmental pressures of the future. As landscape architects and designers look for opportunities to intervene in the climate crisis, the nascent frozen landscapes of northern India present ideas for climate change adaptive design work to build upon.